2021
DOI: 10.51612/teunuleh.v2i2.48
|View full text |Cite
|
Sign up to set email alerts
|

Capital Market Reaction Before and After the Announcement of the First Case of Covid-19 in Indonesia

Abstract: This study aims to determine the differences in abnormal return, frequency of trade, and market capitalization before and after the informations regarding the first reporting of COVID-19 in Indonesia on the Indonesia Stock Exchange. The research population is all companies that entered into Top Leadings in Market Capitalization companies on the Stock Exchange in the period Februari – April 2020, namely as many as 50 companies. The sample in this study was taken using the census method, meaning that the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…The results align with the study by Sari [ 7 ] (2021), which shows a significant abnormal return on one day around the event date, which means that the market reacts to the event. This study's results align with Asmaranti et al [ 33 ], which showed no significant difference in the abnormal return on stocks in Indonesia before and after the tick size change event in May 2016.…”
Section: Analysis and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results align with the study by Sari [ 7 ] (2021), which shows a significant abnormal return on one day around the event date, which means that the market reacts to the event. This study's results align with Asmaranti et al [ 33 ], which showed no significant difference in the abnormal return on stocks in Indonesia before and after the tick size change event in May 2016.…”
Section: Analysis and Discussionsupporting
confidence: 89%
“…The empirical study in Pakistan by Mahmood et al [ 6 ] shows a significant relationship between political events and stock market returns. The results of a study conducted by Sari [ 7 ] showed that there were significant differences in abnormal return (AR), trading volume activity (TVA), and market capitalization before and after the announcement of information regarding the first reporting of the COVID-19 pandemic in Indonesia. Prasojo [ 8 ] studied the stock market reaction to the announcement of the global financial crisis in mining companies.…”
Section: Introductionmentioning
confidence: 99%